2009
DOI: 10.3233/nre-2009-0479
|View full text |Cite
|
Sign up to set email alerts
|

A review of corticospinal tract location at corona radiata and posterior limb of the internal capsule in human brain

Abstract: The corticospinal tract (CST) is the most important motor pathway in the human brain, therefore, the accurate estimation of the CST state following brain injury would enable us to predict the motor outcome or enable accurate surgical planning. The corona radiata (CR) and the posterior limb of the internal capsule (PL) are important locations because they are related to poor motor outcome. In this study, we reviewed the available literature regarding the location of the CST at the CR and PL in the human brain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Other DTI studies have found correlations with personality traits and white-matter indices in the corpus callosum and corona radiata (see, for example, Bjørnebekk et al, 2012;Parkinson & Wheatley, 2014;Xu & Potenza, 2012); however, most studies refrain from discussing these findings. Findings observed in both the corpus callosum and corona radiata are difficult to interpret because the two tracts radiate out, reaching a vast number of cortical areas (Aboitiz, Scheibel, Fisher, & Zaidel, 1992;Fitsiori, Nguyen, Karentzos, Delavelle, & Vargas, 2011), and because current knowledge about these fiber tracts is mostly limited to motor functioning (see Jang, 2009;Kim & Pope, 2005; Y. M. Song, 2007;Wahl & Ziemann, 2008). Overall, with these broad regions, it is difficult to make specific interpretations linking the tracts to distinct types of cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Other DTI studies have found correlations with personality traits and white-matter indices in the corpus callosum and corona radiata (see, for example, Bjørnebekk et al, 2012;Parkinson & Wheatley, 2014;Xu & Potenza, 2012); however, most studies refrain from discussing these findings. Findings observed in both the corpus callosum and corona radiata are difficult to interpret because the two tracts radiate out, reaching a vast number of cortical areas (Aboitiz, Scheibel, Fisher, & Zaidel, 1992;Fitsiori, Nguyen, Karentzos, Delavelle, & Vargas, 2011), and because current knowledge about these fiber tracts is mostly limited to motor functioning (see Jang, 2009;Kim & Pope, 2005; Y. M. Song, 2007;Wahl & Ziemann, 2008). Overall, with these broad regions, it is difficult to make specific interpretations linking the tracts to distinct types of cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of overt and clinically important motor and sensory findings in a patient with a lesion involving the anterior two-thirds of the ICp of sufficient import to produce subcortical aphasia and other neuropsychiatric disturbances is quite unexpected and, to our knowledge, is previously unreported. Rare variant locations of descending and ascending white matter pathways, 3,4,8 including a shift of the pyramidal tract within the ICp to a relatively more posterior location, are associated with atypical patterns of motor involvement after capsular stroke. [8][9][10] Given the location of this patient's capsular lesion, she is suspected of bringing this type of variant capsular anatomy to her stroke.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, it appeared that the deterioration of the pre-existing right hemiparesis was ascribed to the injury of the right anterior CST following the new right pontine infarct, for the following reasons. First, the patient had been diagnosed with an infarct in the left MCA territory 7 years ago, involving whole CST in the left corona radiata [18]. Before the onset of the new right pontine infarct, the patient was able to walk independently and move his right arm partially.…”
Section: Discussionmentioning
confidence: 99%